Cardiac surgeon and electrophysiologist shoulder-to-shoulder approach: Hybrid room, a kingdom for two. A zero mortality transvenous lead extraction single center experience. (15th March 2019) - Roberto, Maurizio; Sicuso, Rita; Manganiello, Sabrina; Catto, Valentina; Salvi, Luca; Nafi, Matteo; Casella, Michela; Rossi, Fabiana; Grillo, Francesco; Saccocci, Matteo; Gasperetti, Alessio; Cervellione, Rosario; et al.
Abstract: Background: Nowadays, transvenous lead extraction (TLE) is considered an essential technique in lead management strategy. Since 2011, a multidisciplinary approach was undertaken in our centre involving electrophysiologists, cardiac surgeons and anaesthesiologists to improve cross- unit cooperation and minimize complications and mortality. The present paper reports procedural outcomes and complications of our lead extraction experience. Methods: We retrospectively collected and analysed data from all consecutive patients undergoing cardiac implantable electronic device leads TLE at the IRCCS Centro Cardiologico Monzino between January 2011 and November 2017. Results: One-hundred fifty patients (111 males, 68 ± 13 years) underwent extraction procedures. The most common extraction indication were infections (86.7%) and TLE was carried out by laser-based approach in 88 (58.6%) patients, by mechanical dilating sheaths in 58 (38.7%) patients and by a combined approach (TLE + open surgical intervention) in 4 (2.7%) patients. Procedural success was obtained in 146 (97.3%) cases with only 3 (2.0%) major complications with 2 cases of structural injury with tamponade requiring emergent median sternotomy. Open surgery extraction was required in 4 patients, after an attempt to TLE, due to leads strict adhesion to cardiac or vascular structures, whereas in 5 (3.3%) cases, the treatment of choice was a combined approach consisting in transvenous leads extraction followed by planned surgery. Conclusions: TLE is a complex procedure that sometimes leads to fatal complications. In our single center experience, a multidisciplinary approach involving electrophysiologist, cardiac surgeon, anaesthesiologist in an operating room allows a safer approach and major complications treatment. Highlights: A new procedural setting in the management of transvenous lead extraction with a well-defined "extraction team". A routine patient risk assessment and pre-operative strategy planning carried-out by a multidisciplinary "extraction team". Lead extraction customary performed in hybrid room equipped with cardiopulmonary by-pass and perfusionist staff on site.